Continuously adjusting CRT therapy: clinical impact of adaptive cardiac resynchronization therapy. (May 2014) - Houmsse, Mahmoud; Abraham, William T
<x xml:space="preserve">Abstract</x> Cardiac resynchronization therapy (CRT) is a well-established therapy to reduce morbidity and mortality in patients with moderate and severe symptomatic congestive heart failure. Left ventricular (LV) pacing that fuses with intrinsic right ventricular (RV) conduction results in similar or even better cardiac performance compared to biventricular (Biv) pacing. Optimal programming of the atrio-ventricular (AV) and inter-ventricular (VV) delays is crucial to improve LV performance since suboptimal programming of AV and VV delays affect LV filling as well as cardiac output. CRT optimization using echocardiogram is resource-dependent and time consuming. Adaptive CRT (aCRT) algorithm provides a dynamic, automatic, ambulatory adjustment of CRT pacing configuration (Biv or LV pacing) and optimization of AV and VV delays. aCRT algorithm is safe and efficacious for CRT-indicated patients without permanent atrial fibrillation. It has been shown to improve CRT response and reduce morbidity and mortality for patients with normal AV conduction.